Little bear. - Minarik, Else Holmelund; Sendak, Maurice (New York, Harper, 1957)
Little Bear$1 (Bs four adventures include taking a trip to the moon and having a birthday party.s
Keywords: Bears -- Fiction; Mothers and sons -- Fiction